Penerapan Model Pembelajaran Interaktif dengan Media Miniatur Untuk Peningkatan Hasil Belajar IPA Sekolah Dasar - Bayu Widiyanto (Bidayatuna, 2020)
Science is a subject that studies the cause and effect of events that occur in nature, science learning involves students playing an active role in finding concepts. So that we need a learning model and learning media that can make it easier for students to find a concept. Miniature media is a learning medium that can be used in learning for students to understand concepts.